(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The new class on bornology, which it is called S*- bornological group are studied, to reduce the boundedness condition for product and inverse maps. This is related structure to bornological group. Also, the certain condition for any codomain of S*-bornological group to be bornological group are given. The result important main, that every bornological group is S*-bornological group. Additionally, every left (right) translation is S*-bornological isomorphism.